Українсько-грузинське військове співробітництво: козацькі традиції та тенденції доби російсько-української війни - Музичко, О. (Чорноморська минувшина, 2024)
Метою даної статті є дослідження історичної перспективи співпраці українців та грузинів у найважливішій сьогодні сфері – військовій. Завдання статті – встановити основні етапи співпраці, коло учасників та окреслити подальші перспективи. Комплекс оповідно-документальних матеріалів дозволяє виділити основні завдання дослідження. Історіографія цього питання має дві помітні складові: загальну та спеціальну. Дійдено висновку, що головним здобутком сучасної історіографії є поняття «скріплені кров’ю», яке вдало відображає суть військової співпраці українців і грузин, а тим більше – бойового братерства. Найінтенсивнішим етапом українсько-грузинського співробітництва тривалий час залишався період 1917–1921 рр. У цей час став очевидним головний ворог українців і грузинів – росіяни. Протягом всієї радянської окупації військова співпраця була унеможливлена і процвітала лише в еміграції. Під час Другої світової війни найбільша кількість грузинів та українців воювала у складі радянської армії, але набагато важливішою для формування традицій національного військового співробітництва є участь грузинів у боротьбі УПА. Сучасна епоха українсько-грузинської співпраці нагадує нам спіраль історії – ми знову маємо відбивати вторгнення російського ворога. Сьогодні обидві нації мають власну державність і більший ступінь підтримки з боку міжнародної спільноти, хоча й поки що недостатньої. Один із головних уроків історії грузинського та українського народів можна висловити у влучному вислові: «Мир – це не відсутність війни, це відсутність Москви». The purpose of this article is to study the historical perspective of cooperation between Ukrainians and Georgians in the most important field today - the military. The objectives of the article are to establish the main stages of cooperation, the circle of people involved, and outline further prospects. The complex of narrative and documentary materials allows us to highlight the main research tasks. The historiography of this issue has two notable components: general and special. Thus, the main achievement of modern historiography is the concept of “bonded by blood”, which successfully reflects the essence of military cooperation between Ukrainians and Georgians, and even more so – of fighting brotherhood. The most intense stage of Ukrainian- Georgian cooperation for a long time remained the period of 1917–1921. At this time, the main enemy of Ukrainians and Georgians – the Russians – became evident. Throughout the Soviet occupation, military cooperation was made impossible and only flourished in emigration. During World War II, the largest number of Georgians and Ukrainians fought as part of the Soviet army, but much more important for the formation of traditions of national military cooperation is the participation of Georgians in the struggle of the UPA. The modern era of Ukrainian- Georgian cooperation reminds us of the spiral of history – we must again repel the invasion of the Russian enemy. Fortunately, today both nations have their own statehood and a greater degree of support from the international community, although still insufficient. One of the main lessons of the history of the Georgian and Ukrainian peoples can be expressed in the apt saying: "Peace is not the absence of war, it is the absence of Moscow".